Portable Ethylene Oxide Sterilization Chamber - Songer, J. R. (1969)
A portable ethylene oxide sterilization chamber was designed, constructed, and tested for use in the sterilization of embolectomy catheters. The unit can accommodate catheters up to 40 inches (101.6 cm) in length and can be operated for less than 4 cents per cycle. A constant concentration of 500 mg of ethylene oxide per liter of space and holding periods of 4 and 6 hr at 43 and 22 C, respectively, were adequate when tested with B. subtilis spores. The estimated cost of construction was $165.00. If temperature control is unnecessary, the cost is approximately $80.00.